2020
DOI: 10.1302/2046-3758.910.bjr-2020-0097.r1
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral as a drug-seeking moiety and a waste dump

Abstract: Bone is a dynamic tissue with a quarter of the trabecular and a fifth of the cortical bone being replaced continuously each year in a complex process that continues throughout an individual’s lifetime. Bone has an important role in homeostasis of minerals with non-stoichiometric hydroxyapatite bone mineral forming the inorganic phase of bone. Due to its crystal structure and chemistry, hydroxyapatite (HA) and related apatites have a remarkable ability to bind molecules. This review article describes the accret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“… 36 However, bone minerals and apatite also serve as a dumping ground for trace elements and drugs, which seriously affects the bone health. 38 Vitamin D3 supplementation decreased the relative abundance of Escherichia Shigella in the upper gastrointestinal tract. 37 Further, Yang et al 39 found that Shigella flexneri could induce robust inflammasome activation in mouse bone marrow macrophages.…”
Section: Discussionmentioning
confidence: 99%
“… 36 However, bone minerals and apatite also serve as a dumping ground for trace elements and drugs, which seriously affects the bone health. 38 Vitamin D3 supplementation decreased the relative abundance of Escherichia Shigella in the upper gastrointestinal tract. 37 Further, Yang et al 39 found that Shigella flexneri could induce robust inflammasome activation in mouse bone marrow macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Bone is a dynamic tissue, and bone homeostasis is maintained by numerous cells and factors. 34 , 35 GJIC in osteocytes plays a critical role in regulating signal transmission among different bone cells and maintaining bone homeostasis. 6 , 7 , 36 Emerging evidence has shown that osteocyte GJIC is impaired during the ageing process, which is closely associated with elevated levels of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the broadly studied inorganic material mesoporous silica nanoparticles (MSNs) have shown great applicational advantages in antitumor therapy with good stability, high drug loading, and high degree of customization for applicability ( Baek et al, 2015 ). The most common strategy is to use the unique hydroxyapatite component of the bone, the pharmacokinetic profile can be significantly enhanced and potentiate the skeletal deposition of the drug by combining bone affinities with therapeutic agents ( Raina et al, 2020 ). Since 1986, when the concept of “bone targeting” was put forward, bone targeting research has advanced considerably ( Pierce and Waite, 1987 ).…”
Section: Introductionmentioning
confidence: 99%